(untitled) - U Tietze (Rome, 2000)
Contrary to the assumed golbal, the number of coastal fishers has started to decline or stagnate in four of the countries studied, while it is still increasing, although more slowly, in the other two. Also contrary to other reports, levels of fertility and infant mortality in fishing communities were found not to be much higher than those in farming communities. However, adul mortality data seem to indicating that living and health conditions in fishing communities could be worse than average, in particular for women.
Keywords: fisheries